Intervertebral Foramen Width Is an Important Factor in Deciding Additional Uncinate Process Resection in ACDF—a Retrospective Study - Sun, Baifeng; Xu, Chen; Zhang, Yizhi; Wu, Shenshen; Wu, Huiqiao; Zhang, Hao; Shen, Xiaolong; Zhang, Zifan; Yuan, Wen; Liu, Yang (Frontiers in Surgery, 2021)
Background: Anterior cervical discectomy and fusion (ACDF) has been established as a classic procedure for the management of cervical radiculopathy. However, it is unclear whether combined uncinate process resection (UPR) is necessary for treating cervical radiculopathy. Here, we investigated the clinical outcome of ACDF combined with UPR compared to ACDF alone to determine the necessity of UPR in treating cervical radiculopathy. Hypothesis: Uncinate process resection may be necessary in certain patients along with ACDF to achieve better clinical outcomes of cervical radiculopathy. Patients and Methods: Fifty-five patients underwent ACDF with UPR, and 126 patients without UPR were reviewed. The width and height of the intervertebral foramen were measured by 45° oblique X-rays. We also measured the Japanese Orthopedic Association (JOA) score and visual analog scale (VAS) score. C2-C7 Cobb angles were obtained from all patients preoperatively and postoperatively. Meanwhile, linear regression analysis was used to evaluate the relationship between the clinical outcomes and the intervertebral foramen width before surgery. Results: Linear regression analysis indicated that the improvement in the JOA and VAS scores was irrelevant to both the preoperative width of the intervertebral foramen (wIVF) and the height of the intervertebral foramen (hIVF) in the ACDF+UPR group. However, preoperative wIVF was associated with postoperative JOA and VAS scores in the ACDF alone group. Those with preoperative wIVF less than 3 mm in the ACDF group had the least improvement in postoperative clinical symptoms due to the change in wIVF (P>0.05). The ACDF group whose wIVF was over 3 mm showed similar clinical outcomes to the ACDF+UPR group, and wIVF significantly increased postoperatively (P<0.05). The fusion rate and C2-C7 Cobb angles did not show significant differences between the two groups (P>0.05). Discussion: Our current findings suggest that UPR should be considered when wIVF is less than 3 mm preoperatively. However, there is no need to sacrifice the uncovertebral joint in ACDF when the preoperative wIVF is over 3 mm. Level of evidence: Level III